Sizes of Soil Chip Cut By a Continuously Operating Planting Hole Digging Machine with an Active Tillage Unit - Beloev Hristo; Long Nguyen Duc; Nhu Dau The; That Nguyen Duc (Acta Technologica Agriculturae, 2022)
Planting hole digging is a minimal tillage method, which is beneficial in terms of reducing energy consumption and preventing erosion. Current popular planting hole diggers work intermittently, which results in low productivity. A continuous-operating hole digging machine with an active tillage unit can solve this issue. However, the theoretical basis for this type of digger has not yet been developed; this is also true for the issue of determining the chip thickness – one of the main technical characteristics which significantly influences energy and agrotechnical indicators of active soil tillage. This paper presents research results of determining the soil chip cut thicknesses and observing of new cutting surface under a continuous operation of hole digging machine with an active tillage unit. At the same time, impacts of factors such as the number of knives and the kinematic factor on soil chip sizes are studied. The soil chip size determination and investigation of influence of kinematic and structural parameters on it is conducted via numerical simulation using MATLAB software. The key factors include kinematic factor λf and the number of knives on one cross-section of the tiller’s rotor Z. When λf and Z increase, the maximum average thicknesses decrease gradually; and vice versa, the new specific cutting surface decreases almost linearly. The results are considered a basis for the selection of final parameters for the construction and operation of one machine to meet agronomic requirements.